Current research and application of stem cells in the dog and cat - ANATOLITOU, A.A.; SIDERI, K.I.; PRASSINOS, N.N. (Journal of the Hellenic Veterinary Medical Society, 2021)
Stem cells (SCs) are multipotent cells with differentiation and proliferation capacities in many cell lineages. The majority of literature applications are about bone marrow derived stem cells (BMSCs) and adipose derived stem cells (ADSCs). Most clinical trials have been done for the treatment of musculoskeletal and neurological problems in canine patients. Hematopoietic SCs (HSCs), synovium (SDSCs) and cartilage (CSPCs) - derived SCs, umbilical cord blood-derived SCs (UCSCs), muscle, dental, cardiac and hepatic SCs have been used with promising results. Despite the overall progress crucial questions about SCs remain unanswered. It is still unclear if the regeneration mechanism of SCs owed to their differentiation into specific progenitor cells or due to their immunomodulatory and anti-inflammatory secretions. Also, there are questions about the best origin of stem cells, whether they should be delivered in situ or systemically, if they should be embedded into scaffolds or not and which is the suitable transplantation stem cells number. Many of the published studies have limitation regarding to sample size, blind randomization, control groups and homogeneity of population. In addition,the long-term efficacy and safety of MSCs need further evaluation. This review is an update in usage of SCs, mainly focused on BMSCs and ADSCs in small animals and its purpose is to present the late developments in this field. Also, the advantages, the disadvantages and the limitations of the current literature review arediscussed.